Teacher's effort in Implementing Peace Education (Study Cases in Class 1 SDN 62 Singkawang) - Widyaningsih, Vivi; Suprapto, Wasis; Mulyani, Sri (International Journal of Research in Education, 2024)
Peace education is one of the methods used to cultivate love and peace in the middle of diversity in Indonesia. Study This aim is to know: (1) the efforts of the teacher in applying education peace; (2) inner teacher challenges to implementation of education peace; and (3) inner teacher solutions to overcome challenges. Study This study is qualitative, with observation, interview, and documentation. Research results show that (1) the effort made by the school to give education peace to their students at school is through the method of applying it through learning. Pancasila Education in class low using curriculum independent, as well give motivation before start learning by teachers for operate mission that has been made by the school to create life Love peace environment school; (2) the obstacles is form reception student That Alone when the teacher gives advice , case the occasional bullying happened to students of SDN 62 Singkawang, meanwhile student yay no want to be friends with student others in need special because no continue when invited talk , and also some fighting students _ with Friend peers who don't seldom raises self injury they; (3) solutions offered by the school for overcome challenge in application education n peace is with embed attitude tolerance to diversity in the environment Â school, apply it through activity extracurricular Scouts, as well make regulation or regulations for obeyed by all inhabitant school. Attitude tolerance in the middle of the diversity that exists in SDN 62 Singkawang is already instilled by the school in its students, especially in children in class low, which is class 1.